Fostering Collaborative Synthetic Research in Archaeology. Issue 1 (7th February 2018) - Altschul, Jeffrey H.; Kintigh, Keith W.; Klein, Terry H.; Doelle, William H.; Hays-Gilpin, Kelley A.; Herr, Sarah A.; Kohler, Timothy A.; Mills, Barbara J.; Montgomery, Lindsay M.; Nelson, Margaret C.; Ortman, Scott G.; Parker, John N.; et al.
ABSTRACT: While our fascination with understanding the past is sufficient to warrant an increased focus on synthesis, solutions to important problems facing modern society require understandings based on data that only archaeology can provide. Yet, even as we use public monies to collect ever-greater amounts of data, modes of research that can stimulate emergent understandings of human behavior have lagged behind. Consequently, a substantial amount of archaeological inference remains at the level of the individual project. We can more effectively leverage these data and advance our understandings of the past in ways that contribute to solutions to contemporary problems if we adapt the model pioneered by the National Center for Ecological Analysis and Synthesis to foster synthetic collaborative research in archaeology. We propose the creation of the Coalition for Archaeological Synthesis coordinated through a U.S.-based National Center for Archaeological Synthesis. The coalition will be composed of established public and private organizations that provide essential scholarly, cultural heritage, computational, educational, and public engagement infrastructure. The center would seek and administer funding to support collaborative analysis and synthesis projects executed through coalition partners. This innovative structure will enable the discipline to address key challenges facing society through evidentially based, collaborative synthetic research. Abstract : Si bien nuestra fascinación por entender el pasado es suficiente justificación para garantizar un mayor enfoque en la síntesis, las soluciones a los problemas importantes que enfrenta la sociedad moderna requieren de conocimientos basados en datos que sólo la arqueología puede proporcionar. Aunque usamos el dinero público para recolectar cantidades cada vez mayores de datos, las distintas formas de investigación que pueden estimular conocimientos emergentes en torno al comportamiento humano han quedado rezagadas. Consecuentemente, la inferencia arqueológica, en gran medida, se queda en el proyecto individual. Podemos aprovechar más eficazmente estos datos y avanzar en nuestros conocimientos en torno al pasado de forma tal que contribuyamos a la solución de problemas contemporáneos si adaptamos el modelo pionero del "Centro Nacional para el Análisis Ecológico y la Síntesis" para fomentar la investigación colaborativa para sintetizar la información arqueológica. Proponemos la creación de la "Coalición para la Síntesis Arqueológica", coordinada a través de un "Centro Nacional para la Síntesis Arqueológica, " en los Estados Unidos. La "Coalición" estará compuesta de organizaciones públicas y privadas establecidas, entidades que proporcionarán la infraestructura esencial académica, cultural, computacional, educativa y de participación pública. El "Centro" buscaría y administraría los fondos para apoyar tanto el análisis colaborativo y los proyectos sintéticos, implementado a través de los socios de la Coalición. Esta estructura innovadora permitirá a la disciplina abordar los retos clave que enfrenta la sociedad a través de la investigación sinténtica y colaborativa.